(3fJGFL GdacQ GdeYQH Yf JaGVd GdKeQs - (3GdQhej(B, (3GdUfYGfj, TYHGf Hf Sdje Hf YKeGf GdQhej Ke GdUfYGfi GdeJhai SfI (B1149s ((3eMeO Hf Ydjs)
(3ChdgG (B:s
(3MeOG def CfHJ ChQGb GdTLQ Gdbhd aj GdeTeT hefGaYg (B: (3abGd aj GdeTeT hgh GdSGHb HGfg aj WHYg ehGab (B,, (3dcd ef aj Lhag MQGQI edJgH ThGXgG VqQGQI (B,, (3aEfg jWajgG aj GdMjf s
(3BNQgG (B:s
(3hddUOGY GdMGQ aj GdQhDS HGdNd ajg ZGjI GdJfajS (B,, (3hjRgb GdfaS eY GdCPgGf cTjQL PGc HdG JhGfj (B,, (3jaYdg GdebUhU aj MjGJg Ch LGgd Ch Hb aj f dGjI (B,, (3hGdMeO ddg Ydi GdHdGZs
(3JHUQI GdYfhGf (B:s
(3EjVGM Gdecfhf (B2\621s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\164s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdRQGYI hGdCYTGHs